إدراج الالتزام بالتبصير في إصلاح القانون المدني الفرنسي لسنة 2016 وأثره على نظرية الالتزام في القانون المدني الجزائري. - حاتم ., مولود (unuversity of eloued- جامعة الوادي, 2019)
تتضمن نظرية الالتزام في القانون المدني الجزائري من حيث المصادر: مصادر إرادية ( العقد والإرادة المنفردة) وغير إرادية ( الفعل النافع، الفعل الضار والقانون) إلا أنّ التطور الذي عرفته الحياة الاقتصادية ألقى بظلاله على طبيعة العقود التي أصبحت تتسّم بالتعقيد في بعض المجالات خاصة لما يتعلق الأمر بالمجال المالي والمصرفي، أين يظهر في غالب الأحيان التفاوت بين أطراف العقد من حيث الإحاطة بالعناصر الجوهرية للعقد المراد إبرامه، ما يعرض الطرف الضعيف في العقد إلى مخاطر تعسف الطرف المحترف خاصة أمام ضعف الضمانات القانونية التي توفرها القواعد العامة له قبل إبرام العقد المدني. ما أدى بالمشرع الفرنسي بصدد إصلاحات القانون المدني الفرنسي في سنة 2016 إلى إدراج الالتزامات ما قبل التعاقد بما فيها الالتزام بالإعلام، والتي تستمد قوتها الإلزامية بصفة مباشرة من النصوص القانوني المحدد لها. وبذلك يكون القانون المدني باعتباره مصدر غير إرادي للالتزام هو المصدر المباشر للالتزام بالإعلام قبل التعاقد. الكلمات المفتاحية: القانون المدني الجزائري؛ القانون المدني الفرنسي؛ نظرية الالتزام؛ الالتزامات ما قبل التعاقد؛ الالتزام بالتبصير. Abstract: The doctrine of commitment in the Algerian Civil Code includes in terms of sources: voluntary sources (contract and unilateral will) and involuntary (Beneficial Act, Harmful Act and law), but the evolution of economic life has cast a shadow over the nature of the contracts, which have become complex in some Areas of particular concern to the financial and banking field, where the disparity between the parties to the contract is often seen in terms of the essential elements of the contract to be concluded, exposing the weaker party to the contract to the risk of abuse of the professional party, especially in the face of the weak legal guarantees provided by General rules before the conclusion of the civil contract. The French legislator on the reforms of the French Civil Code in 2016 led to the inclusion of pre-contractual obligations, including the obligation to inform, which derives its compulsory force directly from the specific legal texts. Thus, the Civil Code, as an involuntary source of obligation, is the direct source of the obligation to inform before contracting. key words: Algerian civil code; French civil Code; Commitment theory; pre-contract obligations; obligation to inform.
مقال
Keywords: القانون المدني الجزائري؛ القانون المدني الفرنسي؛ نظرية الالتزام؛ الالتزامات ما قبل التعاقد؛ الالتزام بالتبصير.; Algerian civil code; French civil Code; Commitment theory; precontract obligations; obligation to inform.